2014
DOI: 10.1021/ic402602d
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium(IV) Metallocavitands As Blue-Emitting Materials

Abstract: A series of zirconium-carboxylate metallocavitands with the general formula [(CpZr)3(μ-κ2,O',O″CR)3(μ3-O)(μ2-OH)3]Cl (Cp = cyclopentadienyl; R = C5H4N (5), C6H7N (6), C18H14N (7), and C18H12N (8)) were synthesized in moderate to high yields (40-83%) by reacting the corresponding carboxylic acids 1-4 with Cp2ZrCl2 in a self-assembly procedure at room temperature. The metallocavitands were characterized using (1)H and (13)C NMR spectroscopy and by single-crystal X-ray diffraction. Complexes 7 and 8 exhibit effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…This luminescence was quenched by molecular oxygen upon exposure to air. Noteworthy luminescent properties were reported also for a series of CpZr carboxylate metallocavitands having various appended nitrogen-containing aromatic functional groups, which exhibited a blue-light luminescence in THF solutions . A fundamental contribution to the area of early transition metal-based photoactive compounds was made by Milsmann et al in 2016, when they reported a homoleptic Zr complex with two tridentate 2,6-bis­(pyrrolyl)­pyridine (PDP) ligands, featuring a CT absorption band in the visible region (528 nm) and exhibiting luminescence in solution with quantum yields comparable with the archetypal [Ru­(bpy) 3 ] 2+ cation .…”
Section: Introductionmentioning
confidence: 99%
“…This luminescence was quenched by molecular oxygen upon exposure to air. Noteworthy luminescent properties were reported also for a series of CpZr carboxylate metallocavitands having various appended nitrogen-containing aromatic functional groups, which exhibited a blue-light luminescence in THF solutions . A fundamental contribution to the area of early transition metal-based photoactive compounds was made by Milsmann et al in 2016, when they reported a homoleptic Zr complex with two tridentate 2,6-bis­(pyrrolyl)­pyridine (PDP) ligands, featuring a CT absorption band in the visible region (528 nm) and exhibiting luminescence in solution with quantum yields comparable with the archetypal [Ru­(bpy) 3 ] 2+ cation .…”
Section: Introductionmentioning
confidence: 99%
“…The ligands (L 1 and L 2 ) were synthesized following a slightly modified procedure. 76 To the suspended aqueous solution of isonicotinic acid (1 mmol, 123 mg, 5 mL water), sodium hydroxide (1 mmol, 40 mg) was added to make isonicotinic acid completely soluble in water. The pH of the solution was adjusted 6−7 by adding 2(N) dil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since in this preliminary study we used AuNPs loaded with multiple ODNs, a fairly polydisperse mixture of aggregates was observed ranging from aggregates of 3–4 AuNPs to gigantic aggregates of hundred AuNPs. The controlled-assembly (controlled aggregate size and distance) of SMDH/AuNPs complexes by using AuNPs loaded with single-strand ODN and their structural characterization is currently under investigation. …”
Section: Results and Discussionmentioning
confidence: 99%